Multiple kinesin-14 family members drive microtubule minus end–directed transport in plant cells - Moé Yamada; Yohko Tanaka-Takiguchi; Masahito Hayashi; Momoko Nishina; Gohta Goshima (2017)
Minus end–directed cargo transport along microtubules (MTs) is exclusively driven by the molecular motor dynein in a wide variety of cell types. Interestingly, during evolution, plants have lost the genes encoding dynein; the MT motors that compensate for dynein function are unknown. Here, we show that two members of the kinesin-14 family drive minus end–directed transport in plants. Gene knockout analyses of the moss Physcomitrella patens revealed that the plant-specific class VI kinesin-14, KCBP, is required for minus end–directed transport of the nucleus and chloroplasts. Purified KCBP directly bound to acidic phospholipids and unidirectionally transported phospholipid liposomes along MTs in vitro. Thus, minus end–directed transport of membranous cargoes might be driven by their direct interaction with this motor protein. Newly nucleated cytoplasmic MTs represent another known cargo exhibiting minus end–directed motility, and we identified the conserved class I kinesin-14 (ATK) as the motor involved. These results suggest that kinesin-14 motors were duplicated and developed as alternative MT-based minus end–directed transporters in land plants.